PENERAPAN KOMPRES HANGAT PADA PASIEN RHEUMATOID ARTHRITIS DENGAN MASALAH KEPERAWATAN NYERI KRONIS: PENERAPAN KOMPRES HANGAT PADA PASIEN RHEUMATOID ARTHRITIS DENGAN MASALAH KEPERAWATAN NYERI KRONIS - Happi, M; Wijaya, Arif; Pratiwi, Tiara Fatma; Fatoni, Imam; Roni, Faishol (LPPM STIKes Bahrul Ulum Jombang, 2022)
ABSTRACT Rheumatoid Arthritis is a disease that attacks the joints so that it can cause pain, stiffness, swelling, inflammation, and limited movement. The purpose of this study was to determine the application of warm compresses to rheumatoid arthritis patients with chronic pain nursing problems at UPT PSTW Jombang Regency.This type of scientific research research is a descriptive design approach with a case study approach, the subject used is 2 patients with chronic pain nursing problems. The location was carried out at UPT PSTW, Jombang Regency by giving a warm compress intervention for 10 days which was given 1 time a day and before and after giving a warm compress, the pain scale was measured using NRS, using data collection which includes assessment, determining diagnosis, making interventions, implementing , and evaluate.The results of the case study show that the provision of warm compress therapy can be an alternative therapy to treat chronic pain.The conclusion of this study is that warm compresses can be used as non-pharmacological therapy in patients with rheumatoid arthritis who experience chronic pain nursing problems so that patients avoid paralysis.